Predicting commitment towards organizational change - Hechanova, Ma. Regina (Archīum Ateneo, 2011)
This paper examines the contextual predictors of attitudes toward change. Through a survey of 1962 employees in organizations that have transformed in the past five years, it hypothesized that change management practices, transformational leadership and organizational cultures of innovation and good relationships would predict both perceived value and commitment to change. Further, it proposed that perceived value of change would mediate the relationship of the predictors on commitment to change. Change management and transformational leadership predicted perceived value and commitment to change. Quality of relationships and innovation predicted perceived value but not commitment to change when controlling for firm size. Contrary to hypothesis, perceived value of change only partially mediated the relationship of commitment to change with the predictor variables.